Training Making Milk Ginger for Singgalang Community District Tanah Datar - Indra Hartanto; Resti Fevria (Pelita Eksakta, 2020)
Ginger is a medicinal plant commodity that has good prospects for development. The value of the ginger plant lies in the rhizomes which are generally consumed as warm drinks, herbs and cooking ingredients and raw materials for traditional medicine. Ginger can be processed into drinks and mixed with other ingredients such as milk. Milk becomes a nutritious drink seen from its nutritional composition, which is very much needed for the development of children's bones and to maintain bone density in adults. The development of increasingly advanced technology, so that there are currently efforts to process fresh milk into various forms of processed. The development of this technology is intended so that milk consumption can spread to all walks of life, the amount consumed by the community is also increasing, diversifying processed products according to consumer tastes, and preventing more milk damage. Milk can be processed into various kinds of products, including ginger milk. This form of processed needs to be realized that to process fresh milk into good processed products requires good quality milk such as fresh milk served in fresh form and ginger milk served in warm or cold form.